Proposta de um sistema de simulação e diagnóstico de falhas aplicado a um sistema de produção - Almeida, Diony José de (2014)
This work we presents a proposal a software of simulation and fault diagnosis applied to an automation system. In that task was developed , a case study that contains a problem of industrial automation. The study was used as the source for creating the simulation that follows the specifications of software models, where you can observe the evolution of events through its language and diagnose faults when they occur in one of the machines of the plant. The process of fault diagnosis is based on the rules of diagnosticabilidades presented in the literature. The machines, as well as its restrictions are modeled within the software itself, where the structures of each automaton are defined the caracteristics as observability an the possibility of failure. The tests in the system showed that of the language used can allowing identify fails, checking only for events that occorem after the occurence the fails.